Mean field game model of the impact of reductions in support on faculty research activity - Robert A. Brown (Proceedings of the National Academy of Sciences, 2026)
Every research university has a distribution of faculty research activity that is fueled by the external support from government, industry, and philanthropy. The large decreases in federal support proposed in 2025 by the Administration would dramatically alter the distribution of faculty research activity. Mean field game (MFG) theory is used to model federal support of faculty research assuming that each researcher seeks to maximize their funding according to a specified utility function. Modeling the collection of researchers as a continuum with individual researchers only influenced by the distribution of others—referred to as the mean field—predicts ergodic distributions that represent a Nash equilibrium. Results representing the funding for faculty in colleges of engineering demonstrate that a decrease in overall federal support of the magnitude proposed by the Administration could lead to over half the faculty inadequately funded to support research. The results have important implications to the university research environment and to their strategies for maintaining the vibrancy of their programs.